New records of rare derogenids (Digenea: Hemiuroidea) from Mediterranean sparids, including the description of a new species of Magnibursatus Naidenova, 1969 and redescription of Derogenes adriaticus Nikolaeva, 1966 - Kostadinova, A.; Gibson, D. I. (Systematic Parasitology, 2009)
Records of derogenid digeneans in the Mediterranean and Black Sea region are scarce and tend to be restricted to a small number of host-groups, but especially to sparid fishes. This work reports on the presence of derogenine and halipegine derogenids from two sparids, Diplodus annularis (L.) and D. sargus (L.), from off the Mediterranean coast of Spain. Five derogenid forms were recovered. Derogenes adriaticus Nikolaeva, 1966 is redescribed from Diplodus annularis, and Derogenes sp. is described from the same host but differentiated from the former species. Magnibursatus barretti n. sp. is described from Diplodus sargus and distinguished from other species of the genus especially by its smaller body size and smaller eggs. M. bartolii Kostadinova, Power, Fernández, Balbuena, Raga & Gibson, 2003 is redescribed from D. sargus, a new host for this species. A single specimen from D. sargus, somewhat similar to M. minutus Kostadinova, Power, Fernández, Balbuena, Raga & Gibson, 2003, is also described, as it exhibits some morphometric differences from the latter species.